Exam ref 70-483 : programming in C♯ - Miles, Rob (Pearson Education, 2019)
Prepare for the latest versions of Microsoft Exam 70-483 and help demonstrate your real-world mastery of modern C# programming. Designed for experienced C# developers ready to advance their status, Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the MCSA level. Focus on the expertise measured by these objectives: Manage program flow Create and use types Debug applications and implement security Implement data access This Microsoft Exam Ref: Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Assumes you have experience programming essential business logic with C# for diverse application types, hardware, and software platforms For details on requirements for taking Exam 70-483 go to https://www.microsoft.com/en-us/learning/exam-70-483.aspx.